Formal (4+1) Cycloaddition of Methylenecyclopropanes with 7‐Aryl‐1, 3, 5‐cycloheptatrienes by Triple Gold(I) Catalysis1. Issue 51 (4th June 2014) - Wang, Yahui; Muratore, Michael E.; Rong, Zhouting; Echavarren, Antonio M.
Abstract 7‐Aryl‐1, 3, 5‐cycloheptatrienes react intermolecularly with methylenecyclopropanes in a triple gold(I)‐catalyzed reaction to form cyclopentenes. The same formal (4+1) cycloaddition occurs with cyclobutenes. Other precursors of gold(I) carbenes can also be used as the C1 component of the cycloaddition.